Design of experimental folding roofs under wind and earthquake load factors - Morales-Guzmán, Carlos Cesar (Corporación Universitaria del Caribe, CECAR., 2020)
The following research was developed on folding roofs, where the issue of load factors in said roofs was addressed, since this type of structures is not fully regulated, so experimental load combinations are contemplated for the design of non—passable roofs, which are established in the Federal District Construction Regulations (RCDF—2014), and the CFE wind design manual (MDVCFE—2015). Combinatorial loads are reviewed with a software called WinTess, which performs structural simulations considering a structural membrane as a stiffener. The result will be the dimensioning of the structure.